Evaluation of Agricultural Waste Management Mechanism in Iran - Zargaran Khouzani, Mohammad Reza; Dehghani Ghahfarokhi, Zahra (Tecno Scientifica Publishing, 2022)
The unfavourable situation of waste management in Iran can be seen in different sectors, and agriculture is not excluded from these sectors. The wastes of the agricultural industry can be used in a beneficial way in various agricultural applications and other industrial processes. However, the cost of collection, processing, and transportation can be much higher than the income from the beneficial use of such waste. Incineration of crop residues creates numerous environmental problems. The most important side effects of burning crop residues include the emission of greenhouse gases that lead to global warming, air pollution, and things like soil degradation, loss of soil fertility, loss of beneficial microorganisms, intensification of soil erosion, etc. In the current research, which is a review based on library sources, the mechanism of agricultural waste management in Iran has been evaluated. There are other consequences of such actions. The criteria for action are laws regarding the burning of product residues in Iran, the most important of which are the Waste Management Law and the Clean Air Law. Among these methods are sustainable management methods for product residues, including compost production, biochar production, and waste management at the production site.